"Who We Are Matters": Exploring Teacher Identities Through Found Poetry (LEARNing Landscapes, 2008)
This paper presents the use of found poetry as a means for exploring teacher identity and argues for its broader use in educational research for studying and representing teachers’ identities and values. This project is grounded in narrative inquiry and feminist standpoint theories and presents three identity poems created with teachers working in Canadian secondary schools. The author suggests that by gaining a better understanding of how teachers understand themselves and their multiple identities in the classroom, scholars, teacher educators, and school leaders can better formulate curricular interventions, staff development programs, and policy initiatives that will work more effectively with classroom teachers to improve students’ experiences in school.
Keywords: arts; found poetry; teacher identity; feminist; narrative inquiry; secondary school